2019
DOI: 10.3892/mmr.2019.9911
|View full text |Cite
|
Sign up to set email alerts
|

Potential urine biomarkers for gestational hypertension and preeclampsia

Abstract: Differential proteomic technology was used to identify urine proteomic profile of gestational hypertension and preeclampsia. Urine samples were collected from 10 patients with gestational hypertension, 10 patients with mild preeclampsia, 10 patients with severe preeclampsia and 10 normal pregnancies and analyzed by 2-D difference gel electrophoresis, then matrix assisted laser desorption ionization mass spectrometry was used to identify differential proteins. Subsequently, ELISA was used to verify the content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Plasma ET-1 is associated with hemodynamic changes during normal pregnancy. ET-1 showed no significant difference in the first and second trimester, but increased significantly in the third trimester, interacting with other vasoactive substances to regulate blood pressure and hemodynamic changes [ 34 – 37 ]. In this study, the levels of NO and SOD increased in both groups after treatment, and the experimental group was significantly higher than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma ET-1 is associated with hemodynamic changes during normal pregnancy. ET-1 showed no significant difference in the first and second trimester, but increased significantly in the third trimester, interacting with other vasoactive substances to regulate blood pressure and hemodynamic changes [ 34 – 37 ]. In this study, the levels of NO and SOD increased in both groups after treatment, and the experimental group was significantly higher than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, early preeclampsia with or without HELLP (hemolysis, elevated liver enzymes, and a low platelet count) syndrome was associated with an increased placental perlecan expression that showed a positive correlation with maternal vascular malperfusion [176]. In contrast, the findings by Guo et al showed decreased perlecan concentration in urine when compared the gestational hypertension group with controls, indicating glomerular filtration barrier injury and renal dysfunction [177]. Collectively, these observations paint a complex and underexplored role for perlecan in hypertension in the cerebrovasculature and beyond.…”
Section: Perlecan and The Cerebrovasculature In Disease And Strokementioning
confidence: 95%
“…As such, the urinary content of around 50 different specific proteins is different in preeclampsia than in normal pregnancy – a focus of current research using urinary proteomics (Guo et al . ) to discriminate between types of gestational hypertensive disorders.…”
Section: Cardiovascular and Renal Characteristics Of Preeclampsiamentioning
confidence: 99%